Simplifying
-10x + -19 = 19 + -8x
Reorder the terms:
-19 + -10x = 19 + -8x
Solving
-19 + -10x = 19 + -8x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '8x' to each side of the equation.
-19 + -10x + 8x = 19 + -8x + 8x
Combine like terms: -10x + 8x = -2x
-19 + -2x = 19 + -8x + 8x
Combine like terms: -8x + 8x = 0
-19 + -2x = 19 + 0
-19 + -2x = 19
Add '19' to each side of the equation.
-19 + 19 + -2x = 19 + 19
Combine like terms: -19 + 19 = 0
0 + -2x = 19 + 19
-2x = 19 + 19
Combine like terms: 19 + 19 = 38
-2x = 38
Divide each side by '-2'.
x = -19
Simplifying
x = -19